The Impact of 2020 Low Traffic Neighbourhoods on Fire Service Emergency Response Times, in London, UK - Anna Goodman; Anthony A. Laverty; Asa Thomas; Rachel Aldred (Findings)
Between March and September 2020, 72 ‘Low Traffic Neighbourhoods’ (LTNs) were implemented in London. We examined the impact on fire brigade emergency response times in October 2020-February 2021 (‘post’), as compared to the same months in the previous two years (‘pre’). We found no evidence that response times inside the LTNs or on boundary roads were affected (e.g. pre/post change for first engine: -14 seconds inside LTNs; -11 seconds in the rest of London; p=0.4 for difference). Fire crews reported more delays due to 'traffic calming measures' in LTNs, but this was entirely offset by a decrease in delays for other reasons, particularly 'traffic'. This was true both in LTNs that predominately blocked motor traffic using physical barriers (e.g. planters) and in LTNs using camera enforcement. These findings add to evidence that LTNs do not adversely affect emergency response times.